Sistem Pendukung Keputusan Menentukan Karyawan Terbaik Dengan Metode AHP - Anita Sindar R M Sinaga (JISKA (Jurnal Informatika Sunan Kalijaga), 2018)
Giving the best employee nicknames to spur other employees competing to provide the best, especially service to customers. Many things affect productivity and quality and comfort in the working environment. Then there needs to be clear and objective criteria in determining the best employees, not just based on qualitative values. In order to award the right target, the method for decision support systems can be applied in determining the best employees. The Analytical Hearachy Process (AHP) method requires criteria in making a decision so that the best employees can be chosen more quickly and objectively. There are 4 criteria: Attitude, Attendance, Performance and Work Period. of the 4 alternatives (4 employees) obtained by SRI RAHAYU: 0.419 or 41.9%, most deserve to be the best employee.